Strategic foresight, knowledge management, and open innovation: Drivers of new product development success - Muhammad Faraz Mubarak; Giedrius Jucevicius; Mubarra Shabbir; Monika Petraite; Morteza Ghobakhloo; Richard Evans (Journal of Innovation & Knowledge)
To remain competitive and make effective decisions in increasingly challenging markets, firms must integrate internal and external knowledge by embedding knowledge management strategies and technologies into their operations. This study aims to examine the roles of strategic foresight and knowledge management in promoting open innovation and driving new product development. Grounded in the knowledge-based view (KBV) of the firm, it investigates how strategic foresight influences open innovation processes and how knowledge management catalyzes innovation success. Using structural equation modelling (SEM) on data collected from 298 technology-based firms located in Lithuania (n = 142) and Slovakia (n = 156), the study demonstrates that strategic foresight directly impacts open innovation and significantly improves new product development through open innovation; in addition, knowledge exploration and exploitation are shown to play important roles in open innovation, with balanced effects on new product development outcomes. The study identifies open innovation as a critical mechanism that links strategic foresight and knowledge management to improve new product development, extending the KBV of the firm by highlighting the integration of external knowledge with internal processes, particularly in smaller, emerging economies. Practically, managers are recommended to prioritize foresight and balanced knowledge management practices while leveraging strategic alliances and networks to improve new product development outcomes. This integrated approach highlights the importance of collaborative innovation and external knowledge in achieving competitive advantage in dynamic business environments.